EKSPLORASI DAN IDENTIFIKASI Trichoderma spp. DI UNIVERSITAS TEUKU UMAR - Lola Adres Yanti; Miru Ajro Love Frianos (Universitas Teuku Umar, 2018)
<Trichoderma sp. is land microorganisms which saprophyte and naturally strike pathogens and beneficial for the plant. Trichoderma sp. could hinder the growth of some plant diseases such as Rigidoporus lignosus, Fusarium oxysporum, Rhizoctonia solani, Sclerotium rolfsi. In addition, as the ability to control pathogen, Trichoderma sp. give positive effect on rhizosfer, the growth of plants, and plants production. This research aimed to identifying Trichoderma spp. in University of Teuku Umar. The methodology are exploration, isolation, and macroscopic and microscopic observation. The research showed that the similarity of Trichoderma spp. at FKM, FP, FT, and Rectorat were Trichoderma sp. 1 and Trichoderma sp. 2. On UF of peat and alluvial land only had Trichoderma sp. 1. Keywords: Different location, exploration and identification, Trichoderma spp.